A New Design of a Wideband Miniature Antenna Array - Oulhaj Otman; Naima A. Touhami; Mohamed Aghoutane; Abdelmounaim Belbachir Kchairi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this work, we present a new configuration of a new miniature microstrip antenna array having a wide frequency band and with a circular polarization. The bandwidth is about 2GHz for a reflection coefficient under -10dB and centered on the ISM ‘Industrial Scientific Medical’ band at 5.8 GHz. To design such array, we have started the design by validating one antenna element at 10 GHz and after that by using the technique of defected ground, we have validated the antenna array in the frequency band [4 GHz -6 GHz] which will permit to miniature the dimensions. The final fabricated antenna array is mounted on an FR4 substrate, the whole area is 102.48 X 31.39 mm2  with a gain of 5dBi at 4GHz.